2015
DOI: 10.4028/www.scientific.net/msf.821-823.553
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Trifluoride Gas Transport and Etching Rate Distribution in Silicon Carbide Dry Etcher

Abstract: A SiC dry etcher using chlorine trifluoride (ClF3) gas was evaluated, particularly about the etching rate distribution. At 100%, the etching rate was high in the center region and was low in the outer region. However, that at 20% showed the opposite profile. This difference was considered to be due to the chlorine trifluoride gas distribution which was built above the gas distributor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…[3][4][5][6][7][8][9] Additionally, the chlorine trifluoride gas could etch a large-diameter wafer using a large scale etcher. 10 For practically applying such a high rate etching technique for electronic device fabrication, the silicon carbide surface after the etching should be carefully studied. Previous studies [3][4][5][6][7][8][9] have reported that the silicon carbide surface often had a carbon film residue after the chlorine trifluoride etching.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Additionally, the chlorine trifluoride gas could etch a large-diameter wafer using a large scale etcher. 10 For practically applying such a high rate etching technique for electronic device fabrication, the silicon carbide surface after the etching should be carefully studied. Previous studies [3][4][5][6][7][8][9] have reported that the silicon carbide surface often had a carbon film residue after the chlorine trifluoride etching.…”
mentioning
confidence: 99%
“…These previous studies using a polycrystalline 3C-silicon carbide wafer showed that the entire etching rate profile depended on the chlorine trifluoride gas concentration. The relationship between the etching rate distribution and the chlorine trifluoride gas concentration has been analyzed and clarified by means of the numerical calculations accounting for the transport phenomena [4,5] in the reactor. Next, for applying this technique to the power device fabrication process, the 4H-silicon carbide should be evaluated [7].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] In this reactor, the entire etching rate profile over the 50 mm-diameter polycrystalline 3C-silicon carbide wafer depended on the concentration and flow of the chlorine trifluoride gas. Based on a numerical calculation accounting for the transport phenomena, 14,15 the relationship between the local etching rate profile and the chlorine trifluoride gas transport was determined. For further development, the single-crystalline 4H-silicon carbide wafer should be used for evaluating the influence of the chlorine trifluoride gas transport.…”
Section: 17mentioning
confidence: 99%
“…In this study, as an extension of previous studies, [13][14][15][16] the C-face 4H-silicon carbide single-crystalline wafer was etched using the chlorine trifluoride gas. The relationship of the etching rate profile with the chlorine trifluoride gas supply was studied using a significantly deep etching condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation